The Effect of Economic Growth, Minimum Wage, Human Development Index on Open Unemployment Rate in West Nusa Tenggara(2019-2023) - Saputra, Deni Darma (Journal of Finance, Economics and Business, 2025)
This study examines the impact of economic growth, minimum wage, and the Human Development Index (HDI) on the open unemployment rate in West Nusa Tenggara Province, Indonesia, from 2019 to 2023. Using a quantitative descriptive approach with panel data regression, the analysis covers 10 districts/cities over a five-year period. The Fixed Effect Model (FEM) was selected based on the results of the Chow and Hausman tests. The findings indicate that economic growth has a negative and significant effect on the open unemployment rate, suggesting that increased economic activity can contribute to job creation. In contrast, the minimum wage and HDI do not show a significant impact on unemployment. The simultaneous F-test, however, reveals that all three variables collectively have a significant influence on the open unemployment rate. The adjusted R-squared value of 0.621 implies that the model explains a substantial portion of the unemployment variation. The results highlight the importance of fostering inclusive economic growth to effectively reduce unemployment, while suggesting that wage and development policies require complementary labor market strategies to be impactful.